REFORMULASI HARTA SEBAGAI SUMBER ZAKAT DALAM PERSPEKTIF ULAMA KONTEMPORER (UIN Sunan Kudus, 2015)
Khazanah Islamic jurisprudence provide us with different definitions of charityexpressed by the scholars and the point is redemption rights are required ona particular property, which cater to certain mandatory based on the haul(deadline) and nishab (minimum). Wisdom itself that is prescribed alms tocleanse the wealthy and property by paying attention to the fate of those whoneed to contribute in realizing the benefit of religion and race. Neverthelessterhadp type of property as a source of zakat or with other terms treasurecompulsory zakat differences of opinion among scholars both scholars of theSalaf and contemporary scholars. The differences are based on their respectivearguments in the text of Al-Aqur’an interpret and Al-Hadith of the charity. Forthat in addressing the variety of ulama regarding compulsory zakat treasure,it is essential to us to understand comprehensively the various aspects offeredprimarily legal reasons used by scholars in setting property as a source of zakat.